Determining the optimal testing parameters on the abrasive wear behaviour of FeCr-reinforced iron-based composites - Ay, M.; Caydas, U.; Hascahk, A. (Sage Publications Ltd, 2010)
This article presents an experimental study of abrasive wear characteristics of FeCr-reinforced iron-based composites produced by the powder metallurgy technique. The wear process parameters are optimized for minimum weight loss based on L-9 Taguchi orthogonal design with three wear parameters, namely the FeCr reinforcement ratio, particulate size, and applied loads. Wear tests were carried out using a pin-on-disc type of apparatus. The orthogonal array, signal-to-noise ratio, and analysis of variance are employed to investigate the optimal testing parameters. The experimental results demonstrate that the applied load was the major parameter among the controllable factors that influence the weight loss of composites. The microstructures and compositions of produced composites are also studied with the help of scanning electron microscopy, light optical microscopy, energy dispersive spectrograph, and X-ray diffraction analysis. Finally, the optimal combination of the testing parameters was determined. A good agreement between the predicted and actual weight loss was observed within +/- 5 per cent.
Keywords: abrasive wear; iron-based composite; Taguchi method